Perbedaan kemampuan pemecahan masalah matematika siswa menggunakan model pembelajaran contextual teaching learning (CTL) dengan model pembelajaran problem based learning (PBL) pada materi segiempat - Bakoban, Faizah Ibrahim (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
This study aims to see whether students' mathematical problem solving abilities using the Contextual Teaching and Learning (CTL) model are better than the Problem Based Learning (PBL) model in the field of questions in class VII SMP Negeri 35 Medan T.A 2016/2017. This type of research is quasi-experimental. The population in this study were all students of class VII SMP N 35 Medan consisting of 8 classes with an average number of 35 people. Sampling was done by cluster sampling by taking 2 classes from 9 classes randomly, namely the experimental class 1 which amounted to 32 people and the experimental class 2 amounted to 32 people. The instrument used to determine students' problem solving abilities is a validation test of problem solving abilities in the form of a description. From the results of the study show that students' mathematical problem solving abilities through the learning model CTL (Contextual Teaching and Learning) are more effective than PBL (Problem Based Learning).